2021
DOI: 10.1097/tp.0000000000003854
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Oxygenated Rewarming Compensates for Cold Storage–induced Dysfunction in Kidney Grafts

Abstract: Background. Normothermic machine perfusion (NMP) provides a promising strategy for preservation and conditioning of marginal organ grafts. However, at present, high logistic effort limits normothermic renal perfusion to a short, postponed machine perfusion at site of the recipient transplant center. Thus, organ preservation during transportation still takes place under hypothermic conditions, leading to significantly reduced efficacy of NMP. Recently, it was shown that gentle and controlled warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
3
18
0
1
Order By: Relevance
“…The latter observation is in line with previous reports, indicating controlled oxygenated rewarming to mitigate rewarming injury upon reperfusion in vitro [ 11 ], in vivo [ 10 ], and in clinical kidney transplantation [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The latter observation is in line with previous reports, indicating controlled oxygenated rewarming to mitigate rewarming injury upon reperfusion in vitro [ 11 ], in vivo [ 10 ], and in clinical kidney transplantation [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to cell culture experiments, which do not allow for functional evaluation of the whole organ, our model strictly mimics the clinical ex vivo graft perfusion and provides functional data on early reperfusion outcome at the whole organ level. Although no long term evaluation of graft function has been possible in the present study, nor could interferences of whole blood with the post-ischemic tissue be accounted for, close similarities of functional data after COR could be found between the present study and earlier investigations in vivo [ 10 ]. Apart from this, the primary goal of the present study, i.e., to decipher the mechanistic role of early mitochondrial dysfunction, triggered upon abrupt warm reperfusion after cold storage and its prevention by controlled oxygenated rewarming could be sensibly addressed by the used model.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…More recently, a porcine auto-transplantation model demonstrated that while 8h of NMP improves renal function compared to SCS, a similar improvement in renal function is observed when cold-stored kidneys are subjected to 2 h of COR [49]. The authors speculate that this may be a useful application given the current requirement for hypothermic storage in the logistics of organ transport.…”
Section: Normothermic Machine Perfusionmentioning
confidence: 90%